Physiological Aspects Identification of the Aloe Vera Grown at Sukoharjo and Wonogiri District, Central Java - Eskundari, Ratna Dewi; Rokhimah Hanik, Nur; Harsono, Sri (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
The aloe vera is known as an ornamental plant that can survive almost all elevations and has a myriad of benefits for humans. This plant can plant at various altitudes, including in the districts of Sukoharjo and Wonogiri. This study aimed to identify the physiological and morphological aspects of aloe vera (Aloe vera) planted in Sukoharjo and Wonogiri districts. Parameters measured were ambient temperature, leaf length, number of stomata, and transpiration rate. Stomata number parameters were calculated using the leaf extension count method under a microscope, while for transpiration rate analysis, cobalt chloride paper was used. The results of this study showed no significant differences in the parameters of average temperature, leaf length, number of stomata, and transpiration rate. The results of this study can be used as a suggestion, especially for Sukoharjo district policy makers, that the aloe vera plant has the potential to become one of the leading agricultural commodities.